The changes in the mechanical properties of neat and SBS-modified HMA pavements due to traffic loads and environmental effects over a one-year period - Karakas, Ahmet Sertac; Sayin, Baris; Kuloglu, Necati (Elsevier Sci Ltd, 2014)
There is a great need for an extensive examination of the performance of asphalt concrete pavements which is made from hot mix asphalt (HMA) since recently there has been an increasing need for roads to parallel the increase in the number of vehicles on the roads. The present study focuses on determining experimentally and numerically the changes in the mechanical properties of neat and SBS modified asphalt mixes exposed to traffic loads and environmental effects over a one-year period. In order to achieve this purpose, in the first part of the experimental study, conventional asphalt tests were carried out in relation to the aggregate and bitumen constituting neat and SBS modified HMAs, and the physical properties of the materials used in HMA were determined and compared to the limits of the related specifications, so that their compatibility to the standards were examined. In the second part of the experimental study, 48 core samples for 4 sample types (NM, NT, SK and ST) were collected from the road side and the vehicle wheel passing line of the asphalt concrete pavement was produced by using neat and SBS modified HMA at specific times over a one-year period and they were examined with Marshall stability-flow tests and performance test; thus, their mechanical properties were determined. In the numerical analysis part of the study, the analyses of 16 models made for 4 sample types were done via Abaqus CAE finite element software, and the changes in the material behaviour under traffic loads and environmental effects over the course of one year was obtained in terms of Von Mises stresses and the data obtained was compared with the experimental data. Finally, the stress-time and ITSM-time relationships for the four sample types were determined via the regression analysis method. The results of the research have revealed that there had been considerable changes in the mechanical properties of the neat and SBS modified asphalt mixture samples, taken at specific times over a one-year period, because of the traffic loads and environmental effects. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: HMA; Traffic loads; Marshall stability test; Performance test; Numerical analysis; Regression analysis